Human resource transformation in the era of Artificial Intelligence (AI) and automation at UIN Syahada - Indah Permasasari Siregar; izzatul Hanifah Harahap; Syifa Amanda Sembiring (Privietlab, 2025)
This research focuses on the transformation of human resources at UIN Syahada in facing the challenges of automation and AI. The lack of sufficient digital skills and the inability of teachers and educational staff to adapt to technological advances are emerging problems in the field. To meet the needs of the digital era, this study aims to identify strategies, policies, and innovations that can be used to improve the competence, professionalism, and ability of educators, educational staff, and students to adapt to digital changes. It also focuses on UIN Syahada Padangsidimpuan's efforts to achieve its vision and mission in the era of higher education digitalization by creating excellent human resources that are globally competitive and have Islamic character, and are capable of utilizing technology morally and productively. A qualitative approach was applied through observation, interviews, and documentary research in UIN Syahada's work units. The findings of this study reveal that digital literacy, technology-based training, and the inculcation of an innovative work culture will effectively transform human resources. This study shows that it is imperative to integrate Islamic values with state-of-the-art technologies in the process of developing superior and flexible human resources in Islamic universities.